(untitled) (Journal of Educational Sciences, 2021)
The article is devoted to the formation of research ethics in Kazakhstan. Since gaining independence, Kazakhstan has made significant progress in reforming education and strives to become internationally competitive in the production of knowledge in the context of internationalization and globalization. Therefore, there is a need to adapt policies on research in education considering international experience, national and cultural context. This article outlines the directions of internationalization of research over the past 10 years. The complex analysis of numerous sources allowed us to identify the problems of the formation of research ethics in Kazakhstan, associated with the slow development of social sciences and qualitative methods of educational research, as well as point out the options for promoting research ethics standards that have the potential to form the competitiveness of Kazakhstani research. To conclude, there is a need for a national discussion on research ethics, training for ethical review, and the creation of Research Ethics Committees. Moreover, it is important to finalize the strategy of the national research ethics code, taking into account the local context compatible with Western standards. This study was financed by Nazarbayev University Collaborative Research Grant “No. 021220CRP0922- Co-creating culturally relevant Social Science research ethics in Central Asia: Mediating local and global influences” for which the authors are grateful. Key words: internationalization, research ethics, educational research, higher education